Perceived Stress, Resilience, and Wellbeing in Seasoned Isha Yoga Practitioners Compared to Matched Controls During the COVID-19 Pandemic - Upadhyay, Preeti; Narayanan, Shilpa; Khera, Tanvi; Kelly, Lauren; Mathur, Pooja A.; Shanker, Akshay; Novack, Lena; Pérez-Robles, Ruth; Hoffman, Kim A.; Sadhasivam, Senthil Kumar; Subramaniam, Balachundhar (Frontiers in Public Health, 2022)
Background Yoga practices, including breathing, meditation, and posture protocols (asanas), have been shown to facilitate physical and mental wellbeing. Methods Seasoned yoga practitioners were recruited from the Isha Foundation. Recruitment of the comparison group was achieved using snowball sampling and were not yoga practitioners. Participants in the non-yoga group were randomized to a 3-min Isha practice or a comparator group asked to perform 15-min of daily reading. Participants completed a series of web-based surveys (REDCap) at baseline, 6, and 12 weeks. These surveys include validated scales and objective questions on COVID-19 infection and medical history. The validated questionnaires assess for: perceived stress (PSS), mood states [anxiety and depression (PHQ-4), joy (DPES-Joy subscale)], mindfulness attention and awareness (MAAS), resilience (BRS), mental wellbeing (WEMWBS) and recovery from traumatic event (PTGI). Weekly activity diaries were employed as a tool for collecting compliance information from study participants. Perceived stress scale scores were identified as primary outcome for this study. Findings The median Perceived Stress Scale (PSS) score for the yoga practitioners compared to the active and placebo comparators was significantly lower at all time-points: baseline: 11 [IQR 7–15] vs. 16 [IQR 12–21] in both the active and placebo comparators (p < 0.0001); 6 weeks: 9 [IQR 6–13] vs. 12 [IQR 8–17] in the active comparator and 14 [IQR 9–18] in the placebo comparator (p < 0.0001); and 12 weeks: 9 [IQR 5–13] vs. 11.5 [IQR 8–16] in the active comparators and 13 [IQR 8–17] in the placebo comparator (p < 0.0001). Among the randomized participants that were compliant for the full 12 weeks, the active comparators had significantly lower median PSS scores than the placebo comparators 12 weeks [10 (IQR 5–14) vs. 13 (IQR 8–17), p = 0.017]. Further, yoga practitioners had significantly lower anxiety at all three-time points (p < 0.0001), lower depression at baseline and 6 weeks (p < 0.0003), and significantly higher wellbeing (p < 0.0001) and joy (p < 0.0001) at all three-time points, compared to the active and placebo comparator groups. Interpretation The lower levels of stress, anxiety, depression, and higher level of wellbeing and joy seen in the yoga practitioners compared to the active and placebo comparators illustrate the impact of regular yoga practices on mental health even during the pandemic. Trial Registration ClinicalTrials.gov, identifier: NCT 04498442.